Pengaruh kaldu jamur terhadap nilai pH, protein dan organoleptik kecap manis nira kelapa - Muhammad Rizky Ramanda; Novi Okta Saputri; Amalia Wahyuningtyas (AGROINTEK, 2024)
Indonesia is one of the largest coconut producer countries in the world. The development of coconut products and their derivatives must be carried out to increase the selling value of processed coconut. One of its uses is to process the sap into soy sauce. Soy sauce is a fermented processed food that is generally made from black soybeans, but in this study, soy sauce will be made using coconut sap. Coconut sap soy sauce is made following with SNI 3543.1:2013. The treatments in this study were ISP (Isolate Soy Protein) with concentration of 1%, a concentration of 2%, and a concentration of 3%, and mushroom broth with concentration of 1%, a concentration of 2%, and a concentration of 3%. The analytical procedures performed were pH test, brix degree test, protein test, viscosity test, hedonic test, and duo-trio test. The test data were analyzed using ANOVA (Analysis of Variance) if there was a significant difference, further tests would be carried out using Duncan's Multiple Range Test (DMRT) with a significance level of 5%.